PENGARUH PEMBIAYAAN MURABAHAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS DENGAN NON PERFORMING FINANCING (NPF) SEBAGAI VARIABEL MODERASI: Studi Empiris Pada Bank Syariah Yang Terdaftar Di Otoritas Jasa Keuangan (OJK) - Purwati Purwati; Fitri Sagantha (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of Murabahah Financing and Musyarakah Financing on Profitability with Non Performing Financing (NPF) as a moderating variable. The independent variable used is Murabahah Financing and Musyarakah Financing then the dependent variable used is Profitability which is proxied by Return On Assets (ROA) and the moderating variable used is Non Performing Financing (NPF). This research method uses quantitative research with an associative approach. The sample in this study is Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) in the period between 2017-2021 in the form of panel data. Data were collected by purposive sampling method. A total of 35 samples that can be processed. Research to test the hypothesis by using multiple linear regression test. The data is processed using the Eviews version 12 software application. The results of this study indicate that partially Murabahah financing has a significant effect on profitability, Musyarakah financing has no effect on profitability, Non-Performing Financing (NPF) is able to moderate the relationship between the influence of murabahah financing on profitability, Non-Performing Financing (NPF) ) is able to moderate the relationship between the influence of musharaka financing on profitability. Then simultaneously or jointly Murabahah Financing and Musyarakah Financing have a significant effect on Profitability